2022
DOI: 10.1155/2022/5610363
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Relationship between Traditional Music in Xinjiang and the Geographical Environment of the Gobi Desert

Abstract: The natural environment and geographical environment provide the possibility for human survival and development and are also the premise of the formation of music culture. When studying the style characteristics and cultural types of music, more comprehensive and correct conclusions can be drawn only when considering various regional factors such as geography and topographic environment. If we want to explore the music of Xinjiang, we must understand the regional culture. The special geographical location of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…[28] Generally speaking, the language of folk songs is the language of folklore, and the thoughts and feelings contained in the dialect and vulgar language also exist in the folk songs. [29] Based on this, Zuoquan Blossom Tune Folk Song is a full embodiment of Zuoquan area folk customs. The next part of the study will focus on the linguistic characteristics of Zuoquan Blossom Tunes in terms of dialect and vulgar language.…”
Section: The Linguistic Characteristics Of Zuoquan Blossom Tunesmentioning
confidence: 99%
“…[28] Generally speaking, the language of folk songs is the language of folklore, and the thoughts and feelings contained in the dialect and vulgar language also exist in the folk songs. [29] Based on this, Zuoquan Blossom Tune Folk Song is a full embodiment of Zuoquan area folk customs. The next part of the study will focus on the linguistic characteristics of Zuoquan Blossom Tunes in terms of dialect and vulgar language.…”
Section: The Linguistic Characteristics Of Zuoquan Blossom Tunesmentioning
confidence: 99%
“…The extremely high artistic pursuit of folk music is more truly reflected in the artistic attainments of the second degree of creation, the ability to draw on the traditional culture, the nutrients of Western music, "foreign for Chinese", without losing its position, faithful to the artistic style of folk music. National music tuning is also a way to show artistic attainments, and basic music tuning is shown in Table 1 [23].…”
Section: The Artistry Of Folk Musicmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%